Analisis Rancangan Antena Telemetri Jenis Dipole pada Unmanned Aerial Vehicle (UAV) - Melvi, Melvi; Shevia, Chiko Ayunindya; Yuniati, Yetti; Batubara, Mona Arif Muda; Ulvan, Ardian; Aryanto, Aryanto (Penerbit Goodwood, 2023)
Purpose: This study focuses on the design and evaluation of dipole antennas for Unmanned Aerial Vehicles (UAVs) operating at a frequency of 433 MHz. The aim is to develop small and lightweight antennas that do not compromise the aerodynamic characteristics of UAVs, ensuring effective communication between the UAV and the Ground Control Station (GCS). Methodology: The research employed CST software to design and simulate dipole antennas using various materials, including copper, gold, silver, aluminum, and iron. The simulation parameters were analyzed in terms of Voltage Standing Wave Ratio (VSWR) values and return loss. Results: The simulation results revealed that the silver antenna material exhibited the best performance, with a VSWR value of 1.3191 and a return loss of -17.222 dB. However, during the fabrication stage, copper was chosen for the antennas, which yielded a VSWR measurement result of 1.427 and a return loss value of -15.09 dB. Subsequent testing of the dipole antenna's communication distance, when placed on a UAV, resulted in a Received Signal Strength Indicator (RSSI) value of -70.68 dBm. This indicated that the antenna maintained a signal quality of 96% at a distance of 2.5 km. Limitation: One limitation of this study is that it primarily focuses on simulations and testing at a specific frequency (433 MHz) and material selection (copper for fabrication). The results may not be directly applicable to different frequencies or materials used in UAV antennas. Additionally, real-world conditions, such as environmental interference, could affect the performance of the antennas. Contribution:This research contributes to the development of efficient and lightweight dipole antennas for UAVs, ensuring reliable communication with GCS. The findings, particularly the choice of copper for fabrication, provide valuable insights for improving UAV communication systems without compromising flight performance.